Visual Storytelling on Instagram by Eco-Print SMEs: Visual Semiotic Analysis and Brand Communication Strategy of Tiva Craft - Ismiyati Hanum; Eko Agung Sugiyarto; MT Ardynata (International Journal Labs, 2026)
The rapid growth of digital platforms has created new opportunities for micro, small, and medium enterprises (SMEs) to strengthen brand identity through visual communication. Eco-print-based SMEs possess unique visual assets derived from natural materials and handcrafted processes; however, these potentials are often underutilized in social media branding. This study aims to analyze how Tiva Craft’s Instagram content constructs brand narratives through visual storytelling and to develop a strategic framework for strengthening eco-print SME branding. A descriptive qualitative approach was employed using Roland Barthes’ visual semiotic analysis. Data were collected from 30 purposively selected Instagram posts from the @tiva_craft account during a one-year observation period. The analysis focused on visual elements, caption narratives, and content patterns at denotative, connotative, and mythological levels. The findings reveal that Tiva Craft’s Instagram content is predominantly oriented toward product documentation, particularly products worn by models during activities and event participation, while content highlighting raw materials, production processes, and product uniqueness remains limited. The visual analysis indicates that existing posts primarily communicate literal product information and have not fully developed deeper brand meanings related to sustainability, craftsmanship, and authenticity. This study proposes a five-dimensional visual storytelling framework consisting of raw materials, creative process, finished products, brand values, and community engagement. The framework can support eco-print SMEs in developing more consistent and meaningful digital brand communication. The study concludes that systematic visual storytelling strategies are essential for transforming eco-print products into distinctive brand narratives on Instagram.